2020
DOI: 10.1101/2020.04.11.20058891
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiological investigation and intergenerational clinical characteristics of 24 COVID-19 patients associated with supermarket cluster

Abstract: Objective: To analyze the epidemiological and intergenerational clinical characteristics of COVID-19 patients associated with cluster, so as to understand the rules of the patients associated with cluster of this outbreak and provide help for the prevention and control of COVID-19. Methods: All close contacts of the patient were screened since the first supermarket employee with COVID-19 was identified. A retrospective analysis was made on the epidemiological and clinical characteristics of the confirmed case… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Diagnosis in all studies was confirmed via RT-PCR and in two cases supplemented with radiological evidence (17,21). Testing of individuals within the study sample varied across settings but was generally very high: all contacts regardless of symptoms (11,13,14,17,18,21); >97% of SNF residents (10,12,15,19,20) and 85.9% of an entire town (16). Length of This article has undergone peer review and been accepted for publication by JAMMI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosis in all studies was confirmed via RT-PCR and in two cases supplemented with radiological evidence (17,21). Testing of individuals within the study sample varied across settings but was generally very high: all contacts regardless of symptoms (11,13,14,17,18,21); >97% of SNF residents (10,12,15,19,20) and 85.9% of an entire town (16). Length of This article has undergone peer review and been accepted for publication by JAMMI.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen articles, nine published and four preprints, from seven countries (China (4), United States of America (USA) (4), Taiwan (1), Brunei (1), Korea (1), France (1) and Italy (1)) that tested 21,708 close contacts of at least 849 confirmed COVID-19 cases, of which 663 were positive and 111 were asymptomatic, met eligibility criteria for the estimation of the primary outcome (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Their sampling frames included residents of skilled nursing facilities (SNF) (10,12,15,19,20); high-risk close contacts of confirmed COVID-19 cases (11,13,14,17,18,21); and a whole district surveillance program in Italy (16). The demographic characteristics (Table 1) indicate that most of the tested individuals were adults, with mean age over 75 years in the five SNF studies and mean over 31 years in the non-aged care studies.…”
Section: Resultsmentioning
confidence: 99%
“…We included four studies that reported on outbreak investigations arising from a single symptomatic person with covid-19 in a chalet in France, 21 a flight from Singapore carrying passengers returning to China, 40 a nursing home in the United States of America, 23 and a supermarket employee in China. 35 The summary estimate of the proportion of asymptomatic SARS-CoV-2 infections was 16% (95% CI 7 to 34%).…”
Section: Figure 1 Forest Plot Of Proportion Of People With Asymptomamentioning
confidence: 98%
“…In nine studies that reported on close contacts of infected individuals and aggregated data from clusters of both asymptomatic and symptomatic people with SARS-CoV-2 the summary estimate was 14% (95% CI 8%-23%, prediction interval 2%-53%) [36,47,60,62,66,72,105,108,111]. We included 12 studies (n = 675 people) that reported on outbreak investigations arising from a single symptomatic person or from the country's first imported cases of people with COVID-19 [32,43,48,58,61,68,71,90,94,95,97,100]. Four of the outbreaks involved nursing homes [58,68,71,94] and four involved occupational settings [43,61,90,95].…”
Section: Proportion Of People With Asymptomatic Sars-cov-2 Infectionmentioning
confidence: 99%
“…We included 12 studies (n = 675 people) that reported on outbreak investigations arising from a single symptomatic person or from the country's first imported cases of people with COVID-19 [32,43,48,58,61,68,71,90,94,95,97,100]. Four of the outbreaks involved nursing homes [58,68,71,94] and four involved occupational settings [43,61,90,95]. The summary estimate of…”
Section: Proportion Of People With Asymptomatic Sars-cov-2 Infectionmentioning
confidence: 99%